Analysis of Problem-Based Learning Model on Mathematical Critical Thinking Skills of Elementary School Studentst - Robert Harianja; Taruly Tampubolon; Lamtagon Manalu (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2023)
PBL is a learning model that leads to strengthening competence of problem-solving, critical reasoning, and learning about learning. The purpose of this study was to determine the significance of the effect of applying the PBL learning model on the critical thinking competence of sixth-grade elementary school students on circle material. The approach applied in this study is a quantitative approach with a pre-test and post-test critical thinking design type. Data collection techniques in this study used critical thinking tests. The participants who were included in this study were 25 students of class VI at SDN 173270, siborong – borong , north sumatera. Data analysis using a one-sample t-test. Based on the calculation of the hypothesis testing is done using the t-test. The normality test results for the value of critical thinking results are 0.139 > ? (0.05) exceeding the significant value, then the variable values are normally distributed, followed by using the one-sample t-test, the t-test results on the equation of the variance section which are assumed to show the Sig value (2)-tailed) < ? ie 0.000 < 0.05 then reject H0. So it can be concluded that there is a significant effect of the application of PBL on the mathematical critical thinking skills of grade VI elementary school students.